1-{[3-(Thiophen-2-yl)-4,5-dihydro-1,2-oxazol-5-yl]methyl}-2,3-dihydro-1H-indole-2,3-dione - Ibtissam Rayni; Youness El Bakri; Jihad Sebhaoui; Khadija El Bourakadi; El Mokhtar Essassi; Joel T. Mague (IUCrData, 2017)
In the title compound, C16H12N2O3S, the indoline and thiophene rings are inclined to one another by 2.01 (2)°. The isoxazole ring adopts an envelope conformation, with the methine C atom as the flap, and its mean plane is inclined to the thiophene and indoline ring mean planes by 19.78 (14) and 20.83 (12)°, respectively. In the crystal, molecules are linked by C—H...O hydrogen bonds involving the same acceptor atom, forming chains propagating along [010]. The chains are linked by further C—H...O hydrogen bonds, forming slabs parallel to the (-303) plane. The slabs are linked by offset π–π interactions [intercentroid distance = 3.792 (1) Å], forming a three-dimensional supramolecular structure.